Research on the autonomous system of the quadruped robot with a manipulator to realize leader‐following, object recognition, navigation and operation. Issue 4 (21st November 2022) - Guo, Jiamin; Chai, Hui; Li, Yibin; Zhang, Qin; Wang, Zhiying; Zhang, Jialin; Zhang, Qifan; Zhao, Haoning
Abstract: A systematic solution is developed to improve the autonomous capability of the quadruped robot with a manipulator, such as navigation, recognition and operation. The developed system adopts novel software, hardware system and system architecture, including a specially designed environment awareness system (EAS). Based on the camera and LiDAR on the EAS, the recognition of multiple common targets, such as the leader, door, window and bag, is achieved. In terms of navigation, a location method is built, that combines the laser odometer and global positioning system. A mapping and path planning module is designed by the Robot‐centric Elevation Mapping algorithm and the rapidly exploring rand tree algorithm. For operation, a real‐time target grasp detection system is proposed based on the You Only Look Once v5 algorithm to improve the success rate of tasks. The whole system is integrated based on the task relevance scheduling strategy to reduce the computational complexity. The tightly integrated system and the subsystems are evaluated by conducting simulations and physical experiments in robot recognition, navigation and operation. Extensive experiments show that the proposed framework can better achieve the autonomous navigation and operation of the quadruped robot with a manipulator. Notably, the proposed framework is still effective when facing dynamic objects. In addition, the system can be easily extended to other forms of mobile robot.